An Assessment of Glutathione-S-Transferase and Lipid Profile in Obese Iraqi Patients - Adnan Mohammed, Nabaa; Muqdad Khaleel, Fayhaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Obesity is a chronic disease that may have genetic, environmental, and other causes. Obesity is a shortcut to many diseases, such as hypertension, diabetes, atherosclerosis, and other chronic diseases. Oxidative stress increases obesity through free radicals. Glutathione S-transferase (GST) is a metabolic enzyme used to remove toxins. This study aimed to determine GST activity in obese patients as a predictor of oxidative stress and the effectiveness of lipid profiling in obese patients. The study included 139 samples of obese and healthy people (obese group 84 and healthy group 55). Both groups (obese and healthy groups) were divided into four groups based on body mass index. Blood samples were collected from obese males and females in Al-Yarmouk Hospital. Some biochemical parameters were measured for all study groups, including estimation of lipid profile, FSG, and GST activity. Results have shown a significant increase in low-density lipoprotein cholesterol (LDL-C) in obese groups and showed a rise in GST levels in healthy groups compared with obese groups (p < 0.05). These studies show that being overweight or obese makes you more likely to get heart disease and other illnesses. It has been demonstrated that the slightly lower levels of GST in the overweight and obese groups compared to other groups demonstrate the precise role of GST in its decrease with weight gain, along with an increase in LDL-C level.